Instagram sebagai Media Pembelajaran Digital Agama Islam di Era 4.0 - Irene Mardiatul Laily; Anita Puji Astutik; Budi Haryanto (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
The purpose of this study is to discuss the use of social media, namely utilizing Instagram features in the delivery of Islamic material, so that this can make Instagram an innovation in Islamic digital learning media. This is motivated by the rapid development of technology in the 4.0 era that requires an educator to be able to use it in the teaching and learning process. This type of research is qualitative research with the chosen approach method being virtual ethnography. Data was collected using documentation and observation on several accounts on Instagram that met the parameters. Data analysis was carried out through the first stages of data reduction, then data presentation, and finally concluding. The results of the study show that the features provided by Instagram can be used as learning media innovations and this is believed to make learning Islamic Religious Education more interesting because the material is presented using different media and ways than usual. Instastory features, feeds, reels, highlights, and Instagram live are some of the Instagram features that can be used as learning media.